Eliciting a historic city’s heritage values ​​through the analysis of its descriptions overtime: An Overview - Moscoso-Cordero, María Soledad (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Heritage values are basic in conservation, nevertheless there is not a methodology to analyze their variation over time and how it has affected the conservation of heritage assets. Therefore, a methodology that allows us to determine their variation in written descriptions about a specific heritage site was needed. In this article we have addressed the concept of heritage values and stressed their importance and their variability over time, but also analyzed different methods from the field of linguistics that would better adapt to determine heritage values variation and their application in the heritage field.